Ex ante Evaluation of the Economic Efficiency of Enterprise Information and Communication Infrastructure Development Projects: A Differentiated Approach - Siedoi, Pavlo (Global Prosperity, 2026)
Enterprise success in the digital economy is largely determined by the availability of necessary conditions for utilizing modern information and communication technologies (ICT). Consequently, the information and communication infrastructure (ICI) of enterprises is constantly evolving through the implementation of relevant projects. This article investigates the problem of evaluating the economic efficiency of enterprise ICI development projects at the justification and preparation stage, specifically the ex-ante evaluation. A wide range of methods exists for conducting ex-ante evaluations of investment projects, which differ significantly in their capabilities. The objective of the article is to formulate a methodological approach for determining the procedure for the ex-ante economic efficiency evaluation of alternative enterprise ICI development projects, taking into account the unique characteristics of the organization. An analysis of scholarly publications was conducted to identify the capabilities of existing methods for evaluating the effectiveness of enterprise ICI development projects. To ensure an individualized approach in selecting the ex-ante economic efficiency evaluation methodology, a conceptual model was developed. The theoretical basis for the proposed model is the Technology-Organization-Environment (TOE) framework. A differentiated approach to determining the most appropriate ex-ante evaluation methodology for projects implementing new technological solutions is ensured by considering five defined groups of factors specific to each enterprise.